2013
DOI: 10.1253/circj.cj-12-1260
|View full text |Cite
|
Sign up to set email alerts
|

Negative Impact of Cardiovascular Risk Factors on Left Atrial and Left Ventricular Function Related to Aortic Stiffness

Abstract: 1490OISHI Y et al. Circulation JournalOfficial Journal of the Japanese Circulation Society http://www. j-circ.or.jp tion, and its relationship with changes in arterial stiffness, namely, LA-LV-arterial coupling. 9 The new angle-independent 2-dimensional speckle-tracking echocardiography (2DSTE) permits the evaluation of not only LA and LV myocardial deformation 9-12 but also aortic and carotid arterial circumferential deformation. 13, 14 The main aim of the present study was to detect earlier the possible effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 33 publications
1
22
0
4
Order By: Relevance
“…19) In the present study, multivariate regression analysis identifi ed age, BMI, SBP, and LV systolic parameters (end-systolic diameter, LVEF, s', and peak systolic radial strain) as independent predictors of LA diastolic stiffness in the comorbid group. Recent studies have demonstrated that subendocardial LA and LV layers along the longitudinal direction and intima and media of large arteries are first and simultaneously impaired by physiologic aging and by CVR factors through various mechanisms, 6,8) and subsequently, a combination of CVR factors leads to a signifi cant and additive negative impact on LA diastolic stiffness related to LV dysfunction and arterial stiffening.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…19) In the present study, multivariate regression analysis identifi ed age, BMI, SBP, and LV systolic parameters (end-systolic diameter, LVEF, s', and peak systolic radial strain) as independent predictors of LA diastolic stiffness in the comorbid group. Recent studies have demonstrated that subendocardial LA and LV layers along the longitudinal direction and intima and media of large arteries are first and simultaneously impaired by physiologic aging and by CVR factors through various mechanisms, 6,8) and subsequently, a combination of CVR factors leads to a signifi cant and additive negative impact on LA diastolic stiffness related to LV dysfunction and arterial stiffening.…”
Section: Discussionmentioning
confidence: 59%
“…6,19) The new angle-independent 2-dimensional speckle-tracking echocardiography (2DSTE) permits the evaluation of not only LA and LV myocardial deformation [6][7][8][9] but also aortic and carotid arterial circumferential deformation. 17,19) This new mo- Values are mean ± standard deviation. § P < 0.05, § § P < 0.01, comparison with control group, * P < 0.05, ** P < 0.01, comparison with 1 risk factor group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common causes of HFpEF are old age, HTN, and cardiac ischaemia but other diseases can also lead to HFpEF [5]. Heart stiffening and decreased filling result in decreased ability of the heart to pump blood to the body [6].…”
Section: Introductionmentioning
confidence: 99%
“…The functional interaction between the LV and arterial tree, termed ventriculararterial coupling, is recognized as a key determinant of cardiovascular performance [10][11][12][13][14]. This arterio-myocardial coupling decline is further precipitated by the presence of other CVD risk factors leading to the development of HFpEF [5,14,15].…”
Section: Introductionmentioning
confidence: 99%